A nice meal turn dangerous: Steakhouse syndrome (Indian Journal of Case Reports, 2020)
Food bolus impaction is one of the most common problems in our population. Most food impaction passes through gastrointestinal spontaneously with only 10–20% requiring intervention. In contrast to true foreign bodies, impacted food bolus in the esophagus is always symptomatic as a result of partial or complete obstruction. We reported a case of food bolus impaction in which the patient presented with odynophagia for 2 days. Prompt resuscitation and endoscopy revealed a food bolus at the distal esophageal. A tactical endoscopic approach is always the best approach for this kind of case.